A Bioinformatics Analysis of the Envelope Glycoproteins Expressing the Hantavirus Cardiopulmonary Syndrome and Hemorrhagic Fever with Renal Syndrome - Polanco, Carlos; Huberman, Alberto; Uversky, Vladimir N.; Castro, Martha Rios; Hernández-Lemus, Enrique; Buhse, Thomas; Alarcón, Gilberto Vargas; Corona, Gabriela Calvo-Leroux; López Oliva, Erika Jeannette; Pimentel-Hernández, Claudia; Martínez-Garcia, Mireya; Becerra-Luna, Brayans; et al. (Current Analytical Chemistry, 2025)
BackgroundThe transmission of hantaviruses through rodents has been associated with the development of severe illnesses, including Cardiopulmonary Syndrome (CPS) and Hemorrhagic Fever with Renal Syndrome (HFRS). Environmental changes impacting rodent populations affect their global distribution. These are severe diseases, potentially lethal, and widespread, making them a public health issue.ObjectiveComputational studies were conducted to better understand the envelope glycoproteins that are expressed by Hantavirus, which produce the cardiopulmonary syndrome and the hemorrhagic fever with renal syndrome.MethodsThe glycoprotein sequences were found through the utilization of specific computational tools, including the Intrinsic Disorder Predisposition (PIDP), Polarity Index Method Profile 3.0v (PIM 3.0v), and genomics software.ResultsExamining the PIM 3.0v profile and the PIDP profile revealed distinct patterns in the envelope glycoproteins of different genotypes of Hantavirus. These patterns allowed for structural and morphological similarities to be identified. In particular, the PIM 3.0v profile shows that it is possible to discriminate between CPS and HFRS groups, and the PIDP profile shows the existence of an overlaid disorder profile of glycoproteins N and C from Hantavirus strains associated with CPS and HFRS.ConclusionUsing the PIM 3.0v profile, our computer programs were able to identify isolates of Hantavirus envelope glycoproteins associated with cardiopulmonary syndrome and hemorrhagic fever with renal syndrome. We believe this research contributes to a deeper comprehension of these emerging viruses.
Keywords: polarity index method 3.0v profile